Doing Business 2014 Regional Profile : Economic Community of Central African States - World Bank (World Bank, Washington, DC, 2014)
This regional profile presents the Doing Business indicators for economies in Economic Community of Central African States (ECCAS). It also shows the regional average, the best performance globally for each indicator and data for the following comparator regions: Southern African Development Community, Economic Community of West African States, Middle East and North Africa, South Asia, and OECD High Income. The data in this report are current as of June 1, 2013, except for the paying taxes indicators, which cover the period January to December 2012. Regional Doing Business reports capture differences in business regulations and their enforcement across countries in a single region. They provide data on the ease of doing business, rank each location, and recommend reforms to improve performance in each of the indicator areas. The report sheds light on how easy or difficult it is for a local entrepreneur to open and run a small to medium-size business when complying with relevant regulations. It measures and tracks changes in regulations affecting 11 areas in the life cycle of a business: starting a business, dealing with construction permits, getting electricity, registering property, getting credit, protecting investors, paying taxes, trading across borders, enforcing contracts, resolving insolvency and employing workers. Doing Business presents quantitative indicators on business regulations and the protection of property rights that can be compared across 189 economies, from Afghanistan to Zimbabwe, over time. The data set covers 47 economies in Sub-Saharan Africa, 33 in Latin America and the Caribbean, 25 in East Asia and the Pacific, 25 in Eastern Europe and Central Asia, 20 in the Middle East and North Africa and 8 in South Asia, as well as 31 OECD high-income economies. The indicators are used to analyze economic outcomes and identify what reforms have worked, where and why.